Out-of-equilibrium electron dynamics of silver driven by ultrafast electromagnetic fields – a novel hydrodynamical approach. (6th March 2019) - Marini, Andrea; Ciattoni, Alessandro; Conti, Claudio
Abstract : We investigate the ultrafast nonlinear response of silver upon excitation by infrared electromagnetic radiation pulses with a duration of a few femtoseconds. Abstract : We investigate the ultrafast nonlinear response of silver upon excitation by infrared electromagnetic radiation pulses with a duration of a few femtoseconds. By adopting the Landau weak coupling approach to account for electron–electron and electron–phonon collisions, we solve the Boltzmann equation through the method of moments obtaining a novel set of hydrodynamical equations describing the ultrafast nonlinear dynamics of electrons in silver. While the novel hydrodynamical model that was obtained reduces to the Drude model for small intensities of the driving field, it predicts that absorption saturates for large but experimentally attainable peak intensities of the order of GW cm −2 . Our results are important for absorption mitigation in plasmonic devices, with potential impact for low-loss plasmonic waveguides and interconnects.